ANALYSIS OF EXPERIENCE OF INTERNATIONALIZATION OF SMALL AND MEDIUM ENTERPRISES OF CHINA - I. Kuznetsov (Вестник университета, 2016)
In the current market situation the development of small and medium enterprises is a key to solve the problem of diversification of foreign economic relations of the Russian Federation, in commodity and geographical slice. The analysis of successful experience of development of foreign economic activity of SMEs in advanced countries, especially in China, and the possibility of its adaptation to Russian conditions is one of the most interesting.